ANALISIS KUALITAS PELAYANAN DI PUSKESMAS BULUSAN KECAMATAN TEMBALANG, KOTA SEMARANG - Deri Izamulardy; Puji Astuti (Journal of Politic and Government Studies, 2026)
The quality of health services is a crucial indicator in assessing public service performance, particularly at primary healthcare facilities such as community health centers. This study aims to analyze the service quality at Bulusan Community Health Center, Tembalang District, Semarang City, based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study employs a quantitative approach with a descriptive design. Data were collected through questionnaires distributed to 100 respondents who were service users, selected using the accidental sampling technique. Data analysis was conducted using descriptive statistics by calculating the mean score of each dimension. The results indicate that the overall service quality is categorized as good, with an average score of 3.02. The highest score is found in the assurance dimension (3.16), while the lowest score is in the responsiveness dimension (2.91). This finding suggests that improvements are needed, particularly in terms of service responsiveness and service speed. This study is expected to provide valuable input for improving the quality of healthcare services at Bulusan Community Health Center.